EVALUATION OF COLLAPSE MECHANISM OF TELECOMMUNICATION TOWER (Nigerian Journal of Technology, 2020)
This paper presents evaluation of a 67.12m high telecommunication tower with the objectives of applying the Finite Element Method (FEM) in modelling it, analysing it under Nigerian wind loads from five different wind zones (Zone 1, Zone 2, Zone 3 Zone 4 and Zone 5 with basic wind speeds as 42m/s, 45.8m/s, 50m/s, 55m/s and 56m/s respectively). The collapse mechanism of the tower was predicted using the Mechanism Method. The tower was modelled and wind load was calculated on it and analysis shows that there is mechanism for the tower to collapse under dynamic wind loads as plastic hinges are developed at the joints and along bracing members. The most severe wind load was used in the plastic analysis conducted and it shows that when the plastic hinges developed at the lower section of the tower, the three mechanisms are more critical compared to when it develops at other sections of the tower. Also, using such load as the collapse load, when the plastic hinges developed at any section of the tower, combine mechanism is more critical and hence the tower is likely to collapse due to failure of both leg members and bracing members. http://dx.doi.org/10.4314/njt.v39i4.9